2017
DOI: 10.1128/aac.00952-16
|View full text |Cite
|
Sign up to set email alerts
|

Population Pharmacokinetics and Target Attainment of Ertapenem in Plasma and Tissue Assessed via Microdialysis in Morbidly Obese Patients after Laparoscopic Visceral Surgery

Abstract: Ertapenem provides broad-spectrum activity against many pathogens, and its use is relevant for the prophylaxis and treatment of infections in morbidly obese patients undergoing surgery. However, its pharmacokinetics and tissue penetration in these patients are not well defined. We assessed the population pharmacokinetics and target attainment for ertapenem in the plasma, subcutaneous tissue, and peritoneal fluid of morbidly obese patients. Six female patients (body mass index, 43.7 to 55.9 kg/m 2 ) received 1,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 48 publications
0
11
0
Order By: Relevance
“…Target engagement of ertapenem was studied in plasma, subcutaneous tissue, and peritoneal fluid, in morbidly obese patients (108). By performing Monte Carlo simulations and population pharmacokinetic modeling of the microdialysis data, it was found that satisfactory concentrations were reached in all sites, albeit with only 25-50% of the unbound plasma concentration in subcutaneous tissue.…”
Section: Systems Pharmacology-related Examples Utilizing Microdialysismentioning
confidence: 99%
“…Target engagement of ertapenem was studied in plasma, subcutaneous tissue, and peritoneal fluid, in morbidly obese patients (108). By performing Monte Carlo simulations and population pharmacokinetic modeling of the microdialysis data, it was found that satisfactory concentrations were reached in all sites, albeit with only 25-50% of the unbound plasma concentration in subcutaneous tissue.…”
Section: Systems Pharmacology-related Examples Utilizing Microdialysismentioning
confidence: 99%
“…Aside from the work described herein, to our knowledge, only three other groups previously utilized nonlinear functions to characterize ertapenem protein binding when conducting ertapenem PK-PD target attainment analyses (30)(31)(32). Additional strengths of these analyses were the utilization of a population PK model which included formally selected covariates and the evaluation of effect-site exposures for patients with HABP/VABP (i.e., ELF AUC values), two considerations which appear to be absent in the available literature describing ertapenem PK-PD target attainment analyses (30)(31)(32)(33)(34)(35)(36)(37). The former consideration allowed for the evaluation of simulated exposures which accounted for the impact of body size and renal function on ertapenem PK.…”
Section: Discussionmentioning
confidence: 99%
“…It is well established that the pharmacokinetics of ertapenem are impacted by body size (11,12,13). Chen et al (11) conducted noncompartmental analyses using the data described herein.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that ertapenem pharmacokinetic parameters differ considerably in obese and morbidly obese patients relative to values in healthy volunteers (11,12,13). However, functions describing these relationships have not been developed.…”
mentioning
confidence: 99%